2022
DOI: 10.1001/jamanetworkopen.2022.0729
|View full text |Cite
|
Sign up to set email alerts
|

Association of Variation in Behavioral Symptoms With Initial Cognitive Phenotype in Adults With Dementia Confirmed by Neuropathology

Abstract: IMPORTANCEBehavioral and psychological symptoms of dementia (BPSDs) in association with amnestic and nonamnestic cognitive phenotypes have not been evaluated across diagnoses of Alzheimer disease pathology (ADP), Lewy body-related pathology (LRP), and mixed pathology (ADP-LRP). OBJECTIVES To determine the clinical phenotypes at the initial visit that are associated with the nature and severity of BPSDs in patients with ADP, LRP, and ADP-LRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…For each participant, the predominant symptom that was first recognized as a decline in the subject's cognition was determined by a clinician at their visit after interview of patient and caregiver and documented in the "NACCCOGF" variable in NACC. Participants were characterized as primary amnestic (if memory was the initial symptom), executive (if the initial symptoms were executive or attention/concentration), language (if initial symptom was language), and visuospatial (if initial symptom was visuospatial) as published previously 19,20 (details in Supplementary Materials). In addition, when present and documented at last clinical visit, the details on the frequency of atypical AD clinical syndrome diagnosis (primary progressive aphasia, posterior cortical atrophy) is provided in the supplementary material.…”
Section: Initial Cognitive Symptoms and Neuropsychological Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each participant, the predominant symptom that was first recognized as a decline in the subject's cognition was determined by a clinician at their visit after interview of patient and caregiver and documented in the "NACCCOGF" variable in NACC. Participants were characterized as primary amnestic (if memory was the initial symptom), executive (if the initial symptoms were executive or attention/concentration), language (if initial symptom was language), and visuospatial (if initial symptom was visuospatial) as published previously 19,20 (details in Supplementary Materials). In addition, when present and documented at last clinical visit, the details on the frequency of atypical AD clinical syndrome diagnosis (primary progressive aphasia, posterior cortical atrophy) is provided in the supplementary material.…”
Section: Initial Cognitive Symptoms and Neuropsychological Testsmentioning
confidence: 99%
“…Examples of these cases include patients with initial language or word‐related difficulties, but not primary progressive aphasia, or initial visuospatial difficulties, but not posterior cortical atrophy 4 . Recent studies of these cases have demonstrated associations between non‐amnestic initial cognitive symptoms and apolipoprotein E ( APOE ) ε4 status 19 and with the risk of onset of behavioral and psychological symptoms of dementia 20 . However, the clinical implication of these initial non‐amnestic cognitive symptoms on longitudinal clinical outcomes remains unknown and is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DLB is ~60% to 70% comorbid with Alzheimer disease (AD)-type pathology, that is, amyloid and tau pathologies, 3,4 and comorbidity with AD-type pathology presents with more severe dementia and has a high risk of mortality 5 . In addition, tau accumulation significantly reduces the occurrence of visual hallucinations, RBD, and parkinsonism 3,4 . Therefore, patients with coexisting DLB and AD-type pathology are often clinically diagnosed with AD due to amnesia without symptoms reminiscent of DLB, 6 and DLB may be overlooked based on clinical symptoms alone.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it has been found that a surprising number of individuals living with dementia do not receive any post-diagnosis support beyond the information they received at diagnosis (2). Indeed, in addition to the symptom of cognitive decline, individuals with dementia frequently manifest behavioral and psychological disturbances like agitation, depression, anxiety, apathy, and delusions, among others (3)(4)(5). It is estimated that 80-90% of patients with dementia develop behavioral and psychological symptoms of dementia (BPSD) during their illness (6).…”
Section: Introduction Rationalementioning
confidence: 99%